Mobile Banking during the COVID-19 Pandemic from Customers' Perspective: A Survey Study for Customers of Banks Operating in the City of Taif - Elmatiri, Djawhara Khalid samrane (Finance and Business Economies Review, 2023)
The study aimed to identify the impact of electronic banking and mobile services dimensions during the Corona pandemic on customers who deal with banks operating in Taif. Know the effect of phone banking during Corona on customer behaviour. The results of the study showed that it found through the analysis that the use of mobile banking services does not require a lot of thinking effort, that it cannot be frustrating, and that mobile banking services are not a difficult way to accomplish banking transactions. It was also found that mobile banking services fit the way the surveyed groups wanted to control their banking movements. Most of them used mobile banking services because they were accustomed to completing all their tasks through their mobile banking during the pandemic